Topographic laser ranging and scanning principles and processing - Shan, Jie; Toth, Charles K. (CRC Press/Taylor & Francis Group, 2009)
"Light Detection and Ranging (LiDAR) is the most important geospatial data acquisition technology to be introduced in recent years. A systematic, in-depth introduction to theories and principles of this groundbreaking technology is long overdue. Professionals in fields ranging from geology, geography, and geoinformatics to physics, transportation, and law enforcement will benefit from this comprehensive discussion of topographic LiDAR principles, systems, data acquisition, and data processing techniques."--Jacket.
Keywords: Lasers in surveying.; Aerial photogrammetry.; elektronické knihy; electronic books